2011
DOI: 10.1103/physreva.84.043815
|View full text |Cite
|
Sign up to set email alerts
|

Spin-to-orbital momentum conversion via electro-optic Pockels effect in crystals

Abstract: In the present work we have demonstrated a possibility for real-time operation by orbital angular momentum (OAM) of optical beams via Pockels effect in solid crystalline materials.Basing on the analysis of optical Fresnel ellipsoid perturbed by conically shaped electric field, we have shown that the point groups of crystals convenient for the conversion of spin angular momentum (SAM) to OAM should contain a three-fold symmetry axis or a six-fold inversion axis. The results of our experimental studies and theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…For example, the angle of rotation of the gyration surface around the Z axis for the group 6mm reads as As shown in the work [15], the conically shaped electric field results in the following coordinate dependences of the electric field components:…”
Section: Topological Defects Of Gyration Tensor Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the angle of rotation of the gyration surface around the Z axis for the group 6mm reads as As shown in the work [15], the conically shaped electric field results in the following coordinate dependences of the electric field components:…”
Section: Topological Defects Of Gyration Tensor Orientationmentioning
confidence: 99%
“…Recently, we have also shown that the TDs associated with the orientation of optical indicatrix in solid-state material media can be induced by various external factors, such as mechanical torsion [12,13] or bending [14]. Moreover, the TDs can be produced by conically distributed electric fields, due to electrooptic Pockels and Kerr effect [15,16]. They can also arise due to piezooptic effect caused by the mechanical strains appearing around structural dislocations in solid crystals [17].…”
Section: Introductionmentioning
confidence: 99%
“…This allows for operating the efficiency of spin-to-orbit angular momentum conversion [9][10][11][12]. Recently we have shown that dislocations of a crystalline structure can also produce the wave front dislocations [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that optical polarization singularities are imposed by structural dislocations existing in crystals or by residual stresses available in glass materials [13]. Moreover, singularities with the strength of topological defects equal to ½ can be induced by conically shaped electric field via the Pockels effect [14].…”
Section: Introductionmentioning
confidence: 99%